Polytrauma: Optimal Imaging and Evaluation Algorithm - Geyer, Lucas L.; Koerner, Markus; Wirth, Stefan; Mueck, Fabian G.; Reiser, Maximilian F.; Linsenmaier, Ulrich (Seminars in Musculoskeletal Radiology, 2013)
Traumatic injuries are the leading cause of death in adults < 45 years of age. Musculoskeletal trauma accounts for a substantial number of injuries in patients sustaining polytrauma. The diagnostic work-up of those patients is challenging, complex, and requires a structured and interdisciplinary workflow. Multidetector CT (MDCT) is considered the imaging modality of choice due to remarkable technical developments in recent years. Besides the evaluation of cranial, chest, and abdominal injuries, MDCT allows for integrated imaging of musculoskeletal trauma within a single CT examination. In this context, CT angiography facilitates the detection of coexisting vascular injuries after trauma of the skeleton. In addition, recent technologies (e.g., dual-energy CT) provide promising applications such as metal artifact reduction. This article summarizes the basic principles of interdisciplinary management of polytrauma patients, reviews recent advances of CT technology that have enabled comprehensive trauma imaging, provides appropriate scan protocols, and discusses the radiologic evaluation of musculoskeletal findings.
Keywords: MDCT; whole-body CT; CT angiography; multiple trauma; musculoskeletal trauma